THE STUDY ON VOLTAGE IMPROVEMENT OF MEDIUM VOLTAGE OVERHEAD WIRE BY TRANSFORMER TAPPING SELECTION - Sambira, Deksa Mahesa Cipy; Junaidi, Junaidi; Kurnianto, Rudi (Faculty of Engineering, Universitas Tanjungpura, 2024)
One of the problems found in the power system is the change or decrease in voltage caused by the power plant center being far from the load center. This study aims to determine the condition of the voltage drop on the Husein Hamzah Feeder and how the use of tap transformers to reduce the voltage drop. The calculation process is simulated using ETAP 19.0.1 software. Based on the simulation results, in the existing condition, the percentage of voltage at the medium voltage bus still meets PLN standards, while at the low voltage bus there are still buses below the standard with a percentage of voltage drop of 3.48%. After making improvements by increasing the transformer tap, the voltage drop value on the bus has decreased to 3.42%. It can be concluded that after making improvements by increasing the transformer tap, the voltage percentage on the rectifier has met SPLN No.72 of 1987 where the percentage of voltage drop does not exceed 5% of the working voltage.